Intermittent hypoxia: a call for harmonization in terminology - Panza, G. S.; Burtscher, J.; Zhao, F. (Journal of Applied Physiology, 2023)
Mild intermittent hypoxia may be a potent novel strategy to improve cardiovascular function, motor and cognitive function, and altitude acclimatization. However, there is still a stigma surrounding the field of intermittent hypoxia (IH). Major contributors to this stigma may be due to the overlapping terminology, heterogeneous methodological approaches, and an almost dogmatic focus on different mechanistic underpinnings in different fields of research. Many clinicians and investigators explore the pathophysiological outcomes following long-term exposure to IH in an attempt to improve our understanding of sleep apnea (SA) and develop new treatment plans. However, others use IH as a tool to improve physiological outcomes such as blood pressure, motor function, and altitude acclimatization. Unfortunately, studies investigating the pathophysiology of SA or the potential benefit of IH use similar, unstandardized terminologies facilitating a confusion surrounding IH protocols and the intentions of various studies. In this perspective paper, we aim to highlight IH terminology-related issues with the aim of spurring harmonization of the terminology used in the field of IH research to account for distinct outcomes of hypoxia exposure depending on protocol and individuum.